Perioperative management of a patient with unexpectedly detected early-stage ovarian mucinous carcinoma combined with progressive bulbar paralysis: a case report and literature review - Dingbei Zhang; Ruibo Xu; Tingting Huo; Ying Liu; Zengfang Hao; Yao Sun; Xiaoyu Xi; Xiaoli Du; Lili Wang; Jiexian Du (BMC, 2024)
Abstract Background Giant ovarian cysts (GOCs)complicated with progressive bulbar paralysis (PBP) are very rare, and no such literature about these cases have been reported. Through the diagnosis and treatment of this case, the perioperative related treatment of such patients was analyzed in detail, and early-stage ovarian mucinous carcinoma was unexpectedly found during the treatment, which provided reference for clinical diagnosis and treatment of this kind of diseases. Case presentation In this article, we reported a 38-year-old female patient. The patient was diagnosed with PBP 2 years ago. Examination revealed a large fluid-dominated cystic solid mass in the pelvis measuring approximately 28.6×14.2×8.0 cm. Carbohydrate antigen19-9(CA19-9) 29.20 IU/mL and no other significant abnormalities were observed. The patient eventually underwent transabdominal right adnexal resection under regional anesthesia, epidural block. Postoperative pathology showed mucinous carcinoma in some areas of the right ovary. The patient was staged as stage IA, and surveillance was chosen. With postoperative follow-up 1 month later, her CA19-9 decreased to 14.50 IU/ml. Conclusions GOCs combined with PBP patients require a multi-disciplinary treatment. Preoperative evaluation of the patient's PBP progression, selection of the surgical approach in relation to the patient's fertility requirements, the nature of the ovarian cyst and systemic condition are required. Early mucinous ovarian cancer accidentally discovered after operation and needs individualized treatment according to the guidelines and the patient's situation. The patient's dysphagia and respiratory function should be closely monitored during the perioperative period. In addition, moral support from the family is also very important.